Transport mechanisms of hydrothermal convection in faulted tight sandstones - G. Yan; B. Busch; R. Egert; M. Esmaeilpour; K. Stricker; T. Kohl (Solid Earth, 2023)
Motivated by the unknown reasons for a kilometre-scale high-temperature overprint of 270–300 ∘C in a reservoir outcrop analogue (Piesberg quarry, northwestern Germany), numerical simulations are conducted to identify the transport mechanisms of the fault-related hydrothermal convection system. The system mainly consists of a main fault and a sandstone reservoir in which transfer faults are embedded. The results show that the buoyancy-driven convection in the main fault is the basic requirement for elevated temperatures in the reservoir. We studied the effects of permeability variations and lateral regional flow (LRF) mimicking the topographical conditions on the preferential fluid-flow pathways, dominant heat-transfer types, and mutual interactions among different convective and advective flow modes. The sensitivity analysis of permeability variations indicates that lateral convection in the sandstone and advection in the transfer faults can efficiently transport fluid and heat, thus causing elevated temperatures (≥269 ∘C) in the reservoir at a depth of 4.4 km compared to purely conduction-dominated heat transfer (≤250 ∘C). Higher-level lateral regional flow interacts with convection and advection and changes the dominant heat transfer from conduction to advection in the transfer faults for the low permeability cases of sandstone and main fault. Simulations with anisotropic permeabilities detailed the dependence of the onset of convection and advection in the reservoir on the spatial permeability distribution. The depth-dependent permeabilities of the main fault reduce the amount of energy transferred by buoyancy-driven convection. The increased heat and fluid flows resulting from the anisotropic main fault permeability provide the most realistic explanation for the thermal anomalies in the reservoir. Our numerical models can facilitate exploration and exploitation workflows to develop positive thermal anomaly zones as geothermal reservoirs. These preliminary results will stimulate further petroleum and geothermal studies of fully coupled thermo–hydro–mechanical–chemical processes in faulted tight sandstones.